Associations of physical activity, alcohol and nicotine consumption with diet types in secondary and tertiary education students: Results of two Austria nation-wide studies - Katharina C. Wirnitzer; Derrick R. Tanous; Mohamad Motevalli; Günther Apflauer; Clemens Drenowatz; Gerhard Ruedl; Werner Kirschner (Bern Open Publishing, 2024)
Introduction & Purpose Based on consensus on the tremendous health benefits through physical activity (PA) & exercise at all ages, it is a sound recommendation for health promotion, maintaining good health and the prevention of non-communicable diseases (NCDs) incl. risk factors. However, since health is a complex state that has to be earned over a lifetime, one single measure to promote sustainably good health seems insufficient, particularly in childhood, adolescence and emerging adulthood since inherited health-related behaviours, habits and lifestyles track over time resulting in (good or worse) the adult state of health. Both studies aimed to investigate health-related behaviours of Austrian secondary pupils and tertiary University/college students, with a focus on PA & exercise (days per week) linked to different diet types (mixed, vegetarian, vegan). Methods From science 2 school (Wirnitzer, n.d.b) and From science 2 highschool & university (Wirnitzer, n.d.a) were designed as interdisciplinary cross-sectional studies, with data collection Austria nation-wide (pupils: academic year 2019/2020; students: summer semester 2021). Participation in these standardized online questionnaires was anonymous and voluntary; based on self-report, data on sociodemographic characteristics and lifestyle characteristics (PA & exercise, diet, alcohol and nicotine) were collected. Both studies were approved by the Federal Ministry of Education, Science and Research and all 9 Austrian Federal Education Authorities. Results In total, 8,799 pupils (63% girls) and 6,148 students (65.3% females) provided complete data sets. Generally, 82.4% of pupils (15.0 ± 2.3 years; 2.9 ± 2.0 days/week) and 79.3% of students (24.8 ± 6.2; 3.6 ± 1.5 days/week) reported PA & exercise as leisure time activity. Compared to non-actives, they showed significantly higher daily intakes of fruit and fluids and less smoking (p < 0.05). A mixed diet was reported by the majority of pupils and students (84.3% at age 15.2 ± 2.2 years and 71.2% at age 25.3 ± 6.9 years) versus vegetarian (8.5% and 22.8%) and vegan diets (7.2% and 6.0%), respectively. In both populations, the vegan diet (3.2 for pupils; 3.9 for students; p < 0.01) was associated with more days/week of PA & exercise compared to vegetarian (2.9 for pupils; 3.4 for students) and mixed diets (2.8 for pupils; 2.9 for students), with a significant increase in leisure sports participation across diet types: up to 86.4% in pupils (p = 0.03) and 92.9% in students (p < 0.01) for the vegan diet. More vegan pupils (74.7%; p = 0.001) and students (32.5%; p < 0.01) reported not drinking alcohol compared to non-vegan pupils (range: 51.2-53.7%) and students (range: 26.7-30.7%), while there was no difference in smoking habits across dietary subgroups. Discussion Both studies were the first to examine the dual approach to sustainable health based on the prevalences of PA & exercise linked to different diet types. Key results are: (1) active vs. inactive pupils and students show lifestyle behaviours more beneficial to health, and (2) vegan vs. non-vegan youth are more active and report healthier behavioural choices. A strength of both studies is that the findings are based on large samples, especially the school study was conducted on a sample size nicely in line with the Austrian WHO HBSC study. Given the detrimental health effects of insufficient PA and poor dietary choices, attention should be focused on policies and educational curricula to improve healthy lifestyle choices, at best through a dual approach to health by permanently combining the personally modifiable and most natural lifestyle factors: (1) regular PA & exercise with (2) a healthy diet, in order to shape better public health by improved individual youth health. Although there is consensus on the tremendous health benefits through PA & exercise as a single measure, lifelong health seems impossible to be achieved by a 1-dimensional approach in the long-term. Conclusion The present research shows an interplay between PA patterns and dietary habits, not only influencing each other but also affecting other health-related behaviors. In this study, especially adopting a vegan diet is linked with healthier lifestyle behaviour, highlighting the importance of healthy dietary choices for overall health and well-being. Therefore, and since there is huge potential left untapped (Figure 1), the promising dual approach to sustainable health is recommended as a minimum and starting point in secondary and tertiary educational settings. References Wirnitzer, K. C. (n.d.a). From science 2 highscool & university. https://uni.science2.school/en/ Wirnitzer, K. C. (n.d.b). From science 2 school. https://www.science2.school/en/